ESTADO DE DERECHO Y RESPONSABILIDAD JURISDICCIONAL EN LA COOPERACIÓN ANTE EL RÉGIMEN DE PROHIBICIÓN GLOBAL DEL TERRORISMO: LA RECIENTE EXPERIENCIA BRASILEÑA - De Aguilar Correa, Eduardo Pitrez; Lima Scalcon, Raquel (Revista de Derecho, 2019)
The article investigates the space of convergence and resistance of national bodies in face of a set of international standards internalized by Brazil that deal directly and indirectly with the problem of terrorism (Law 13.260/2016). Therefore, it explores a set of legal rules that frames the treatment of actions qualified as terrorists, identifying this set of rules as a global prohibition regime that penetrates directly and indirectly in the criminal justice systems of states. Qualified as enemy criminal law, such regime imposes to the domestic bodies of the States, especially Constitutional Courts, the burden of the defense of fundamental principles of Rule of Law, as they are set on International Human Right treaties and national Constitutions (responsibility in cooperation).
Keywords: Human Rights; Terrorism global prohibition regime; Transnational criminal policy; Judicial review